A Critical Review on the Book Strategic Management of Information Systems - Ehsan Karami; Ali Yassini (پژوهش‌نامۀ انتقادی متون و برنامه‌های علوم انسانی)
The Strategic Management of Information Systems book deals with the strategic management of information systems as a complete set for the organization. The purpose of this article, which has been done in a descriptive-analytical method, is to find the strengths and weaknesses of this work. Accordingly, the book has been studied first and then analyzed from three perspectives: content, writing, and form-structure. The book is written as a resource for students of management and especially technology management. According to the author, the work has some goals such as helping and guiding managers to adopt appropriate strategies for managing information systems in organizations, clarifying the various dimensions of information systems and reviewing the most important theories and the most prominent perceptions of information systems management. However, based on the results of the present critique, it seems that the author has not achieved the desired goals in a desirable way. Due to the fact that the book does not have an editor, the work has defective linguistic rules and misuse of writing symbols. From the formal and structural point of view, the chapters of the book lack introduction, goals, and conclusions, or summaries, which confuse the reader. From the content point of view, the topics of the book lack the necessary coherence and accuracy. Some of the general topics and concepts are covered in the book, and there is no balance between the descriptions of some of the proposed topics.